Effects of Preloading of Stannous Compounds on the Distribution of 99mTc-Pertechnetate - Hathorn, L. F.; Greenberg, D. D.; Som, P.; Meinken, G. E.; Sacker, D. F.; Atkins, H. L. (Nuklearmedizin - NuclearMedicine, 1977)
99mTc-pertechnetate distribution studies were performed in rabbits and mice following pretreatment between 5—336 hours with various routinely used stannous complexes (HSA, MAA, GHT, DTPA, PYPs) containing different amounts of Sn++ (0.17 —15.0 μ mg/kg). Beyond a concentration of 0.26 mg/kg of Sn++ an alteration in 99mTc-pertechnetate distribution was observed. The red blood cell was found to be the most prominent target. An in-vivo reduction of 99mTc-pertechnetate apparently occurred by the presence of stannous ion within the red blood cell. Preloading time period between 5—24 hours did not alter the uptake of RBC/plasma ratio. Beyond that period it decreased slowly and still persisted up to 2 weeks following pretreatment. RBC/ plasma ratio of 99mTcO4- increased with increased Sn++ content of various commercially available pharmaceutical kits.